Ecclesiastical control and religious nature of hospital assistance in Seville at the end of the Middle Ages - Pérez González, Silvia María; Arboleda Goldaracena, Juan Carlos (Cuadernos de Historia, 2023)
During the Middle Ages the hospital network in Western Europe reached an extraordinary development. In the case of Seville this hospital expansion was very prominent, since the late fifteenth century had more than a hundred centres. The objective of this study is to demonstrate how the Sevillian secular clergy controlled hospital care in a very prominent way in the city of the Betis river. This translated into a prominent role in the religious nature of Sevillian hospitals, despite the presence of professionals linked to medicine within de hospital staff. In this way the Church of late medieval Seville instrumentalized the assistance needs as an element of its empowerment in the cuty what was to become the port and the gate way to the Indies.